Prevalence and Diagnosis of Celiac Disease in Children - Mayumi Hernández Díaz; Armando Fermín Álvarez Corcuera; Sergio Luis González López (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Foundation: celiac disease is an autoimmune, systemic, chronic condition, induced by gluten proteins that cause damage to the intestinal mucosa in genetically predisposed individuals. This pathology has a high prevalence in pediatric age. Objective: to describe the prevalence and diagnosis of celiac disease in children of the Cienfuegos province. Method: a descriptive, observational, cross-sectional study was conducted in the specialized in celiac disease consultation of gastroenterology, Paquito González Cueto de Cienfuegos University Pediatric Hospital from January 2016 to September 2018. The variables analyzed were: age, sex, color of the skin, municipality of residence, family pathological history, associated diseases, symptoms, signs, hemoglobin, bone age, duodenal intubation and radiography of intestinal transit. Data were obtained from patients' medical records. The percentage of each of them was calculated in relation to the total diagnosed cases. Results: it more frequently diagnosed in children younger than 5 years old. The most frequent associated disease was epilepsy, the serological examination of antitransglutaminase and intestinal biopsy was performed on the total of patients studied with high positivity and lesions that allowed the diagnosis to confirm the condition. A prevalence of the condition of 6.88 per 10 000 inhabitants was estimated. Conclusions: the prevalence of the disease in the studied population was high its classic clinical form prevailed in the diagnosis.